Trust, Growth and Well-being: New Evidence and Policy Implications - Yann Algan; Pierre Cahuc (Institute for the Study of Labor (IZA), 2013)
This survey reviews the recent research on trust, institutions and growth. It discusses the various measures of trust and documents the substantial heterogeneity of trust across space and time. The conceptual mechanisms and the methods employed to identify the causal impact of trust on economic performance are reviewed. We document the mechanisms of interactions between trust and economic development in the realms of finance, innovation, the organization of firms, the labor market and the product market. The last part reviews recent progress to identify how institutions and policies can affect trust and well-being.
Keywords: O11; O43; Z13; 330; trust; growth; institutions; well-being